(untitled) (GnosisWisdom, 2022)
Objective To estimate the effectiveness of the participatory educational intervention "child care" in adherence to anemia treatment in children aged 6 to 23 months in rural households in a region of the Andean trapezium of Peru. Methodology The study was explanatory, the research design was pre-experimental with a single group before and after. The sample consisted of mothers and their children from 6 to 23 months of age; n=30 considering the inclusion and exclusion criteria. For data collection, the survey technique was used whose validated instruments such as the questionnaire to measure the variables of adherence to treatment. Results Before the intervention, 60.0% of mothers with children with anemia state that within the pharmacological treatment they reach adherence, 40.0% do not reach adherence. After the intervention; 86.7% manage to achieve adherence to pharmacological treatment to overcome anemia and 13.3% still do not achieve adherence to pharmacological treatment. Before the intervention, 60.0% of mothers with children with anemia state that within the dietary treatment they reach adherence, 40.0% do not reach adherence. After the intervention; 93.3% manage to achieve adherence to dietary treatment to overcome anemia and 6.7% still do not achieve adherence to dietary treatment. Before the intervention, 50.0% of mothers with children with anemia manifest adherence to treatment against anemia, 50.0% do not reach adherence. After the intervention; 86.7% manage to achieve adherence to treatment to overcome anemia and 13.3% still do not achieve adherence to treatment against anemia in children from rural homes in Huancavelica.